Correlation of Weaning Food with the Event of Stunting to Toddlers in Kali Rungkut Village Surabaya - Warini Ayu Safitri; Noer Kumala Indahsari (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Stunting is a chronic nutritional problem due to several factors and is intergenerational. For the number of children with stunting conditions, Indonesia is ranked fifth globally. This is due to one of the reasons for the provision of less nutritious food during the growth period obtained from weaning food. The purpose of this study was to determine whether there was a relationship between the provision of weaning food and the incidence of stunting in children in Kali Rungkut Village, Surabaya.This study is a case control method of chi square analysis and kappa correlation using primary data, namely questionnaires. The number of samples that meet the criteria are 53 people, then the data is processed with SPSS.Based on the results of the study, the relationship between complementary feeding and the incidence of stunting in Toddlers in Kali Rungkut Village, Surabaya, with a p-value of 0.002 less than (0.05) and an OR of 6.429. Based on the results of the study, it can be concluded that there is a significant relationship between the provision of complementary foods and the incidence of stunting in children under five in Kalirungkut sub-district, Surabaya and the relationship between the provision of complementary foods and the incidence of stunting is a large category, which has a risk of 6,429 times greater in the provision of complementary foods, less good in the incidence of stunting than the provision of complementary foods. the good one.